(untitled) (GYMNASIUM, 2009)
Elaborating theoretical papers, where there dominates the idea of researching and experimentation regarding the tendencies and perspectives of skiing in general, and of alpine skiing in particular, represents one of the major preocupations of the specialists in the domain who, through their activity, push forward the theory and methodics in skiing training, finding the most efficient methods and techniques of initiation and learning. The main goal of the paper in the activity of learning the skiing technique is that of forming into the subjects, through the indirect way, the system of motive abilities and skills that couls allow them a safe and efficient crossing of the areas covered by snow. The topic of the present paper and implicitly of the performed activities for its study emphasized the fact that some elements, not enough elaborated, can be factors that limit the progress of the instructed subjects.